Electronic governance and open society : challenges in Eurasia : 5th International Conference, EGOSE 2018, St. Petersburg, Russia, November 14-16, 2018, Revised selected papers /: challenges in Eurasia : 5th International Conference, EGOSE 2018, St. Petersburg, Russia, November 14-16, 2018, Revised selected papers. (2019) - Unknown
No abstract available